Numerical Simulation of Hydrodynamic Forces on an Underwater Vehicle Near the Free Surface - M. S. Ahmad; M. A. A. Hasnan; N. M. R. Shaharuddin; M. N. A. W. Muhammad Yazid; I. Shah; M. Mohsin (Journal of Applied Fluid Mechanics)
Underwater Vehicles (UVs), including Autonomous and Remotely Operated Vehicles, are increasingly utilized in marine applications such as exploration, surveying, and defense. The hydrodynamic performance of UVs, particularly their resistance and lift characteristics near the free surface, plays a crucial role in their design and operational efficiency. This research employs Computational Fluid Dynamics (CFD) simulations to analyze the behavior of an underwater vehicle operating at various depths near the free surface. Two configurations of the DARPA SUBOFF model: the bare hull (AFF-1) and the fully appended configuration (AFF-8) were investigated. Simulations were conducted under different operating conditions, and numerical results were validated against experimental and existing numerical data to ensure accuracy and reliability. The interaction between the underwater vehicle and the free surface is analyzed to understand its effects on hydrodynamic performance. The findings demonstrate a significant impact of the free surface on resistance and lift, with the appendages in the AFF-8 configuration leading to more pronounced hydrodynamic effects, particularly at higher speeds where wave generation and interaction with the free surface are increased. These results highlight the effects of speed, depth, and vehicle configuration on hydrodynamic performance, providing valuable insights for the design and optimization of UVs. This study serves as a valuable foundation for further exploration of operational strategies and the development of UVs across diverse marine applications.